Analisis Tantangan Belajar Siswa Dalam Materi Interaksi Sosial di Kelas VII SMP Swasta Cendramata - Sumardi, Habibatul Qolbi; Manurung, Sakira Putri; Simamora, Tirza Grass; Sidauruk, Tumiar (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
The title of this study is an analysis of student learning challenges in social interaction material in class VII of cendramata private junior high school. The formulation of the problem in this study is how students' learning difficulties in social studies subjects on Social Interaction material at Cendramata Medan Private Junior High School and how teachers have made various efforts to overcome the learning difficulties experienced by students. This research uses qualitative methods with descriptive research types. Data collection techniques are carried out by interviewing sources who are considered to have valuable knowledge and through documentation. After conducting research, results were obtained that showed that students still experience difficulties in the social studies learning process, especially in social interaction material.